Nanobiosensor for the detection and quantification of specific DNA sequences in degraded biological samples - M. E., Ali; Uda, Hashim, Prof. Dr.; Shuhaimi, Mustafa; Yaakob, Che Man, Dato' Dr.; M. H. M., Yusop (Springer-Verlag, 2011)
Link to publisher's homepage at http://www.springerlink.com/